Pessimistic portfolio allocation and choquet expected utility - Gilbert W. Bassett; Roger Koenker; Gregory Kordas (Centre for Microdata Methods and Practice (cemmap), 2004)
Recent developments in the theory of choice under uncertainty and risk yield a pessimistic decision theory that replaces the classical expected utility criterion with a Choquet expectation that accentuates the likelihood of the least favorable outcomes. A parallel theory has recently emerged in the literature on risk assessment. It is shown that a general form of pessimistic portfolio optimization based on the Choquet approach may be formulated as a problem of linear quantile regression.
Keywords: 330; Portfolio-Management; Erwartungsnutzen